2013
DOI: 10.1007/s11547-013-0946-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI and PET/CT in multiple myeloma patients during staging and after treatment: personal experience in a longitudinal study

Abstract: WB-MRI proved superior to PET/CT in detecting MM, especially in diffuse disease. PET/CT appears to be more sensitive in the assessment of MM after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The impact of MRI on staging patients according to DS Plus has been analyzed in many studies [ 12 14 ]. Although 18 F-FDG PET/CT has been proved to be prognostically valuable in staging different groups [ 15 17 ], only few studies have been reported on DS Plus based on 18 F-FDG PET/CT [ 18 ]. One of the reasons is that no standard interpretation criteria have been proposed for the evaluation of 18 F-FDG PET/CT scans in MM.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of MRI on staging patients according to DS Plus has been analyzed in many studies [ 12 14 ]. Although 18 F-FDG PET/CT has been proved to be prognostically valuable in staging different groups [ 15 17 ], only few studies have been reported on DS Plus based on 18 F-FDG PET/CT [ 18 ]. One of the reasons is that no standard interpretation criteria have been proposed for the evaluation of 18 F-FDG PET/CT scans in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors posited that MR imaging appears to be the superior study in terms of diagnostic performance (54). A prospective study of 22 patients with newly diagnosed multiple myeloma who underwent PET/CT and whole-body MR imaging prior to treatment showed PET/CT findings to be positive in 18 of 22 cases, whereas MR imaging findings were positive in all patients (55). These results again support the diagnostic power of MR imaging.…”
Section: Use Of Mr Imaging and Pet/ct In Staging And Diagnosismentioning
confidence: 84%
“…PET/CT has been found to be more sensitive than MR imaging in treatment assessment. In one analysis, PET/CT helped correctly identify 16 of 20 patients who had a positive response to treatment, compared with only 12 of 20 patients at MR imaging (55). PET/CT also demonstrates much faster normalization of imaging findings than does MR imaging.…”
Section: Use Of Mr Imaging and Pet/ct In Staging And Diagnosismentioning
confidence: 99%
“…Studies have demonstrated that WB-MRI has a greater sensitivity and specificity for detection of focal bone lesions in myeloma compared with both WB-CT ( n = 41) 6 and 18 F-FDG PET/CT ( n = 22). 7…”
Section: Discussionmentioning
confidence: 99%